2006
DOI: 10.1002/cmdc.200500025
|View full text |Cite
|
Sign up to set email alerts
|

Substituted Isoxazoles as Potent Inhibitors of p38 MAP Kinase

Abstract: In a continuous effort to develop improved p38 MAP (mitogen-activated protein) kinase inhibitors, we focused our attention on the suitability of the isoxazole ring as a bioisosteric replacement for the imidazole ring of SB-203580. 3,4- and 4,5-disubstituted as well as 3,4,5-trisubstituted isoxazole derivatives were synthesized. These compounds were tested in an in vitro enzyme-linked immunosorbent assay of isolated p38 MAP kinase and for inhibitory potency against cytochrome P450. Compound 4 a displays a highl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
33
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 43 publications
0
33
0
Order By: Relevance
“…The compound 4-[3-(4-fluorophenyl)isoxazol-4-yl]pyridine displayed a promising anti-inflammatory activity, by suppressing cytokine release, lowering the affinity for cytochorme P450 and showing a decreased in the IC 50 toward isolated p38 MAPK [9]. Another heterocycle with a potential to serve as an anti-inflammatory molecule is the 4,5-dihydroisoxazole, or isoxazoline.…”
Section: Introductionmentioning
confidence: 99%
“…The compound 4-[3-(4-fluorophenyl)isoxazol-4-yl]pyridine displayed a promising anti-inflammatory activity, by suppressing cytokine release, lowering the affinity for cytochorme P450 and showing a decreased in the IC 50 toward isolated p38 MAPK [9]. Another heterocycle with a potential to serve as an anti-inflammatory molecule is the 4,5-dihydroisoxazole, or isoxazoline.…”
Section: Introductionmentioning
confidence: 99%
“…Hepatic toxicity was ascribed to the pyridinyl imidazole derivatives [4]. Hence, subsequent studies were carried out with a broader set of with anticytokine scaffolds more or less similar to the original diaryl imidazole class [4,20,31,[72][73][74][75][76][77][78].…”
Section: Structural Features Of Small Molecule In-hibitorsmentioning
confidence: 99%
“…The respective substituted pyrimidylpyrazoles 13 a and 13 b [23,41] and isoxazoles 14 a and 14 b [42,43] were synthesized to develop the most appropriate scaffold. Biological testing revealed that the inhibitory potency of the sulfanylimidazoles is almost as good as that of the pyrazole scaffold and better than the isoxazole scaffold (Table 2).…”
Section: Biological Assaysmentioning
confidence: 99%